The impact of teacher socio-emotional competence on student engagement: a meta-analysis - Gebre, Zerihun Ayalew; Demissie, Mesfin Molla; Yimer, Berhanu Mekonnen (Frontiers in Psychology, 2025)
Teaching requires significant emotional investment to foster students' engagement. However, studies of teachers' socio-emotional competence (SEC) and student engagement are limited. This research compiles available evidence to clarify the overall effect of teachers' SEC on student engagement. By conducting a comparative search across databases, such as PubMed, Scopus, Web of Science, Google Scholar, and Science Direct, the researchers found 31 related research articles published from 2018 to 2023. Of these, 21 papers satisfied the specified inclusion or exclusion criteria and were quantitative. Data analysis was conducted using JASP software. The study found a weak positive correlation between teachers' socio-emotional competence (SEC) and student engagement without publication bias, indicating a significant impact on professional development and overall student engagement. Moreover, the forest plot indicates the statistical significance of teachers' socio-emotional competence in student engagement, based on various studies in the current literature. The study highlights the crucial role of teachers' socio emotional competence in fostering student engagement, thereby promoting healthy and resilient development. To improve teacher socio-emotional competence and student engagement, nested mixed-method designs and integration of training into professional development programs are recommended. Further research should incorporate mediation or moderation into teacher engagement to strengthen this relationship.